ANALISIS PERBANDINGAN ROA, ROE, NPM, DAN BEBAN OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (Universitas Muhammadiyah Palembang, 2023)
Purpose–This study aims to determine and analyze whether there are significant differences in ROA, ROE, NPM and BOPO at Bank BCA Tbk and Bank MEGA Tbk Design/methodology– Using the comparative analysis method. The research instrument is taken from the annual report of each state-owned company, namely PT BANK BCA Tbk and PT BANK MEGA Tbk, which are listed on the Indonesia Stock Exchange in the form of a financial report data table consisting of a report on Profit After Tax, Own Capital, and Operating Costs for the period 2011-2020. accessed from www.idx.co.id. And each of his websites. The population in this study is all data on the financial statements of Bank BCA and Bank Mega for 20 years from 2000-2020. The sample in this study is data on the financial statements of Bank BCA and Bank Mega for 10 years from 2011-2020. While the sampling technique using proportional sampling. Location The object of this research is located at the Head Office, Menara BCA, Grand Indonesia, Jl, MH Thamrin No. 1, Central Jakarta, JK 10310 Menara Bank Mega Head Office Jl. Captain Tendaen 12 – 14A South Jakarta, JK 12790. Data collection techniques used are documentation and literature study. Data analysis techniques used are Normality Test and Independent Siple t-test. Findings - The results showed that there were differences in financial performance between Bank BCA and Bank Mega in the ratio of ROA and ROE. Meanwhile, for the ratio of NPM and BOPO, there is no difference in financial performance. .